Meta-analysis and moderator analysis of the seroprevalence of hepatitis E in South Eastern Asia - Raji, Yakubu Egigogo; Toung, Ooi Peck; Mohd Taib, Niazlin; Sekawi, Zamberi (Nature Portfolio, 2023)
By 2030, the World Health Organization wants to decrease viral hepatitis incidence and mortality by 90 and 65, respectively. One of the agents responsible for the increased burden of viral hepatitis is the hepatitis E virus (HEV). This emerging pathogen is prevalent worldwide causing both acute and chronic infection. The rising risk profile of HEV has become a source of increased global public health concern. Despite this challenge, South-Eastern Asia (SEA), where many at-risk people are found, lacks uniform HEV prevalence data. Therefore, a meta-analysis was conducted to assess the overall prevalence of hepatitis E in SEA. Using R statistical software, a random effect model was used to estimate the logit-transformed prevalence. Moderator analyses were used to investigate the potential sources of variation. Thirty-two studies comprising 29,944 with 6806 anti-HEV antibody-positive individuals were evaluated. The overall HEV seroprevalence in SEA was 21 (95 confidence interval CI: 17–27) with high heterogeneity. At the country level, Laos has the highest prevalence estimate of 39% (CI: 16–69). Also, the studied population, year of publication, duration of sampling, and diagnostic method are significant HEV prevalence predictors accounting for 22.61% of the observed heterogeneity. The high HEV prevalence found in this study necessitates coordinated national and regional efforts to combat this emerging disease.